PENGARUH KUALITAS LAYANAN, EXPERIENTIAL MARKETING, DAN CITRA DESTINASI TERHADAP KEPUTUSAN UNTUK BERKUNJUNG KEMBALI MELALUI KEPUASAN PENGUNJUNG SEBAGAI VARIABEL INTERVENING (Studi pada Objek Wisata Religi Masjid Agung Banten) - Salsabila Chairunisa; Bambang Muna Dwiyanto (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This research begins with developing a research framework or model between Service Quality, Experiential Marketing, Destination Image, Revisiting Decisions and Visitor Satisfaction. Furthermore, data were obtained from 110 respondents by distributing questionnaires through google forms and consisting of open and closed questions. Respondents are visitors who had visited the Objek Wisata Religi Masjid Agung Banten at least 2 times. Then, the data obtained were analyzed quantitatively and structurally using the Structural Equaition Modeling (SEM) method using the Analysis Moment of Structural (AMOS) program. The results showed that service quality and destination image had a significant impact on visitor satisfaction variables as intervening variables. Destination image had a significant impact on revisiting decisions. Likewise with the intervening variables, namely visitor satisfaction have a significant influence on revisiting decisions. Meanwhile, experiential marketing has a insignificant influence on visitor satisfaction. And the variables of service quality and experiential marketing have insignificant effect on revisiting decisions. It is hoped that the managerial implications of this research can be used as suggestions for improvement for the Objek Wisata Religi Masjid Agung Banten.